Poly(3-hexylthiophene) nanowhiskers filler in poly(ε-caprolactone) based nanoblends as potential bioactive material. (May 2019) - Da Pian, Marta; Maggini, Michele; Vancso, G. Julius; Causin, Valerio; Benetti, Edmondo M.
Graphical abstract: Highlights: P3HT nanowhiskers were efficiently dispersed in a matrix of PCL. PCL triggers a faster assembly/aggregation of P3HT to nanowhiskers. Structurally defined PCL-P3HT nanoblends were obtained. Abstract: The inclusion of a polymeric nanofiller with distinctive optoelectronic properties within a well-processable polymer matrix has enabled the fabrication of a wide range of functional materials. However, most of recent works focused on the characterization of the entire composite, without taking into account the effects of the matrix in the morphology of the nanofillers. This paper reports a comprehensive study about the dispersion of poly(3-hexylthiophene) (P3HT) nanowhiskers (NWs) within a poly(ε-caprolactone) (PCL) matrix, yielding a structurally defined nanoblend that could be applied as photoactive material for tissue engineering. NW formation through P3HT crystallization/aggregation was investigated within anisole solutions of PCL by UV-vis spectroscopy, while the excitation bandwidth and the resonant Coulomb coupling constant were calculated by using a non-isothermal variation of the Avrami's law. The presence of PCL was demonstrated to increase the rate of P3HT crystallization, and determined the assembly of well-defined NWs, featuring a larger conjugation length than that characteristic of nanocrystals obtained from pure P3HT. P3HT-PCL films presented the semicrystalline morphology typical of PCL, with aggregates of P3HT NWs mainly concentrating at the boundaries of PCL spherulites, and thus forming a semiconducting polymer network that expands through a biodegradable polymer matrix.